First direct measurement of the parity-violating coupling of the Z0 to the s quark - Abe, K; Abe, K; Abe, T; Adam, I; Akimoto, H; Aston, D; Baird, K; Baltay, C; Band, H; Barklow, T; Bauer, J; Bellodi, G; et al. (2000)
We present the first direct measurement of As, the parity-violating coupling of the Z0 boson to the strange quark, using ∼550 000 e+e- → Z0 → hadrons events recorded by the SLC Large Detector with a polarized e- beam. We tagged Z0 → ss̄ events by the absence of B or D hadrons and the presence in each hemisphere of a high momentum K± or Ks0. Fitting the polar angle distributions of the strangeness-signed thrust axis gave As = 0.895 ± 0.066(stat) ± 0.062(syst). The analyzing power and uū + dd̄ background were constrained using the data, greatly reducing any model dependence. © 2000 The American Physical Society.